Predicting the trend and utility of different photocatalysts for degradation of pharmaceutically active compounds: A special emphasis on photocatalytic materials, modifications, and performance comparison. (1st September 2021) - Majumder, Abhradeep; Saidulu, Duduku; Gupta, Ashok Kumar; Ghosal, Partha Sarathi
Abstract: The rapid rise in the healthcare sector has led to an increase in pharmaceutically active compounds (PhACs) in different aqueous bodies. The toxicity of the PhACs and their ability to persist after conventional treatment processes have escalated research in the field of photocatalytic treatment. Although different photocatalysts have been successful in degrading PhACs, their inherent drawbacks have severely limited their application on a large scale. A substantial amount of research has been aimed at overcoming the high cost of the photocatalytic material, low quantum yield, the formation of toxic end products, etc. Hence, to further research in this field, researchers must have a fair idea of the current trends in the application of different photocatalysts. In this article, the trends in the use of various photocatalysts for the removal of different PhACs have been circumscribed. The performance of different groups of photocatalysts to degrade PhACs from synthetic and real wastewater has been addressed. The drawbacks and advantages of these materials have been compared, and their future in the field of PhACs removal has been predicted using S-curve analysis. Zinc and titanium-based photocatalysts were efficient under UV irradiation, while bismuth and graphene-based materials exhibited exemplary performance in visible light. However, iron-based compounds were found to have the most promising future, which may be because of their magnetic properties, easy availability, low bandgap, etc. Different modification techniques, such as morphology modification, doping, heterojunction formation, etc., have also been discussed. This study may help researchers to clarify the current research status in the field of photocatalytic treatment of PhACs and provide valuable information for future research. Graphical abstract: Image 1 Highlights: PhACs, with low log Kow exhibited low degradation rate constant. Antibiotics and EDCs were more difficult to degrade as compared to other PhACs. GO and Bi-based photocatalysts showed promising performance under visible light. Fe, Zn, and Bi-based photocatalysts were found to be the most promising materials. Coupling of photocatalysts with other materials improved their performance.